SOFTWARE IMPLEMENTATION OF A DESKTOP INFORMATION SYSTEM FOR LIBRARY AUTOMATION - Morokhovych, V. S.; Pavlyk, D.-I. V. (Systems and Technologies, 2026)
This article describes the development of a desktop solution for the automation of library operations, which optimises the management of the collection, users, book circulation and staff work. The system provides for the authentication of users with the roles of librarian and administrator, with data verification via a secure connection to the database. The application implements functionality for viewing, adding, editing and searching for information about readers, books and loan transactions, with access to certain actions restricted depending on the user’s role. The “Loans” tab supports automatic calculation of service charges based on the duration of book use, determination of book return or loss status, and the imposition of fines for late returns. The administrative section of the system allows you to manage library staff, change passwords, dismiss employees, and update reference information on genres and publishers. The database structure is also described, error handling is implemented, and a reliable connection to the database is ensured. Thanks to its intuitive interface, clear separation of roles, and extensive functionality, the information system significantly improves the efficiency of library operations, ensuring transparency and convenience in day-to-day tasks. The technical methods described can be adapted for use in related fields, such as archival record-keeping, the development of local CRM systems or electronic card catalogues, where the key requirements are autonomy, performance and data security. The primary focus of the application’s development is to expand its functionality whilst maintaining full autonomy and stable operation within a local network. This is particularly important for libraries that do not have constant access to the internet or operate in environments with stringent requirements for data storage on internal media.